Above-Ground Dimensions and Acclimation Explain Variation in Drought Mortality of Scots Pine Seedlings from Various Provenances - Seidel, Hannes; Menzel, Annette (Frontiers in Plant Science, 2016)
Seedling establishment is a critical part of the life cycle, thus seedling survival might be even more important for forest persistence under recent and future climate change. Scots pine forests have been disproportionally more affected by climate change triggered forest-dieback. Nevertheless, some Scots pine provenances might prove resilient to future drought events because of the species’ large distributional range, genetic diversity, and adaptation potential. However, there is a lack of knowledge on provenance-specific survival under severe drought events and on how acclimation alters survival rates in Scots pine seedlings. We therefore conducted two drought-induced mortality experiments with potted Scots pine seedlings in a greenhouse. In the first experiment, 760 three-year-old seedlings from 12 different provenances of the south-western distribution range were subjected to the same treatment followed by the mortality experiment in 2014. In the second experiment, we addressed the question of whether acclimation to re-occurring drought stress events and to elevated temperature might decrease mortality rates. Thus, 139 four-year-old seedlings from France, Germany, and Poland were subjected to different temperature regimes (2012–2014) and drought treatments (2013–2014) before the mortality experiment in 2015. Provenances clearly differed in their hazard of drought-induced mortality, which was only partly related to the climate of their origin. Drought acclimation decreased the hazard of drought-induced mortality. Above-ground dry weight and height were the main determinants for the hazard of mortality, i.e., heavier and taller seedlings were more prone to mortality. Consequently, Scots pine seedlings exhibit a considerable provenance-specific acclimation potential against drought mortality and the selection of suitable provenances might thus facilitate seedling establishment and the persistence of Scots pine forest.